Exposição aguda na câmara hipóxica como preditivo do mal agudo da montanha - Ganme, Gabriel [UNIFESP] (2019)
Background: Thousands of tourists visit high altitude mountains around the world every year. Typically, there is a loss in physical performance at altitude of 3000 meter or higher due to low blood oxygen levels which can lead to AMS. Objectives: Develop a physical evaluation protocol aiming to predict the chance of an individual to develop AMS signs and symptoms and enabling early intervention. Methodology: A pilot project involving seven volunteers on a trekking trail in Everest and the main study encompassing 30 individuals on a three day Aconcágua mountain race. All individuals have been submitted to ergometric and/or ergospirometry test, capillary oximetry, bioimpedance in normoxic conditions and hypoxic chamber ergometric test before the trip, throughout the race the individuals have been monitored through Lake Louise Score, heart rate measurement tests and capillary oximetry test. By the end of the expedition, there was an attempt to establish correlation between AMS signs and symptoms and other findings in the hypoxic chamber with the results in actual altitude by means of statistics methods such as Anova and T-Student. Result: Body mass loss - both lean and fat - has been observed across all the participants in the study. Notwithstanding, the hydration level of the group has remained unchanged. These findings are in line with the current literature on the subject. Furthermore, this study proposes a physical evaluation protocol to be adopted by those willing to ascend to high altitude without compromising their health.